If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(3n+4)=8(9n+5)+1
We move all terms to the left:
7(3n+4)-(8(9n+5)+1)=0
We multiply parentheses
21n-(8(9n+5)+1)+28=0
We calculate terms in parentheses: -(8(9n+5)+1), so:We get rid of parentheses
8(9n+5)+1
We multiply parentheses
72n+40+1
We add all the numbers together, and all the variables
72n+41
Back to the equation:
-(72n+41)
21n-72n-41+28=0
We add all the numbers together, and all the variables
-51n-13=0
We move all terms containing n to the left, all other terms to the right
-51n=13
n=13/-51
n=-13/51
| -6(y-6)=-4y+18 | | 3.5x+5(45-x)=4.5(45) | | 6x+1=6x+14 | | 2(w–6)=3w | | 2-3x3+4=0 | | 3.5x+5(45-x)=4.50(45) | | 22–4f=14 | | 357=20g+75 | | 49t^2-50t=-30 | | 40+14j=2(-4j=13) | | -2r+3=43 | | 5+6(x-2)=4-8(x-4) | | 3x=√2 | | -3+v=-6= | | 36=9-3(x-2 | | -5=4+x= | | 2.6/1.7=n/10.2 | | 8(x+6)+6=-2 | | 2(9x-7)=8 | | 5=x-3/12 | | 1/6=2/5+y | | -7=2-9m | | 36=9-3x-2 | | 11/3+1/4=x | | 0.03x=0.01x+2.9 | | v/v+2+1/v-1=1 | | 2(3x+-3)+x=1 | | -15v-40=1+8v | | 8-2x=14-2x | | 10=2-y+1 | | 3.56x+35.6=71.2 | | 36+2x=-54-3x |